Designing an effective dissolution test for bilayer tablets tailored for optimal melatonin release in sleep disorder management - Bassetto, Rebecca; Amadio, Emanuele; Ciampanelli, Francesco; Perin, Stefano; Ilari, Pietro; Gaballo, Paolo; Callegari, Martina; Feltrin, Sara; Gobbo, Jacopo; Zanatta, Samuele; Bertin, Walter (Frontiers in Nutrition, 2024)
This project aims to investigate the release performance of bilayer tablet (BL-Tablet) designed with both fast and slow-release technology, targeting sleep disorders. The tablet incorporates Melatonin, extracts of Eschscholzia californica and Melissa officinalis. In order to validate the effectiveness of the extended-release profile, an advanced dissolution test was herein proposed. This new method utilizes biorelevant intestinal fluid media and incorporates a stomach-to-intestine fluid changing (SIFC) system. To demonstrate the advantages of employing this method for assessing the controlled release profile of active ingredients, the dissolution results were compared with those obtained using the conventional EU Pharmacopoeia approach. Furthermore, the comparative analysis was extended to include a monolayer tablet version (ML-Tablet) lacking the slowrelease technology. Technological characterization and bioaccessibility studies, including intestinal permeability test, were conducted as well to assess the pharmacological performance and bioavailability of active ingredients. The dissolution data recovered revealed that the two dissolution methods did not exhibit any significant differences in the release of ML-Tablet's. However, the dissolution profile of the BL-Tablet exhibited notable differences between the two methods particularly when assessing the behavior of the slowrelease layer. In this scenario, both methods initially exhibited a similar release pattern within the first approximately 0.5 hour, driven by the fast-release layer of the tablet. Following this, distinct gradual and sustained releases were observed, spanning 2.5 hours for the EU Pharmacopoeia method and 8 hours for the new SIFC-biorelevant dissolution method, respectively.Overall, the novel method demonstrated a substantial improvement compared to conventional EU Pharmacopoeia test in evaluating the performance of a controlled slow-release technology. Remarkably, the prolonged release technology did not have an adverse impact on melatonin intestinal absorption, and, consequently, maintaining its potential bioavailability of around 78%.Concluding, this research provides valuable insights into how the innovative dissolution test can assist formulators in developing controlled release formulations.